CAUSES OF AGGRESSION THAT OCCURS IN ADOLESCENCE AND WAYS TO ELIMINATE IT - Баймахова, Ақнұр; Кошербаева, Айгерим; Әліпбек, Ардақ; Ланин, Борис (Pedagogy and Psychology, 2023)
This article discusses the causes of aggression that occurs in adolescence and ways to eliminate it. When establishing the problem of aggression in adolescents, it is necessary to distinguish between the concepts of «aggression» and «aggressiveness»: the first concept deepens within the framework of a biological pattern, in connection with which the socio-historical situation of aggressiveness of one person or group of persons is determined. The study and study of the essence and content of the directions of interpretation of aggression characteristic of this period is one of the most important problems of our modern society. The causes of aggression arising in adolescence are described in detail, and ways to eliminate it are specified. In childhood, an intense behavioral consciousness of the individual is formed, the mastery of moral and ethical norms of behavior begins to guide the system of value judgments that has arisen in his behavior. Therefore, the situations of self-esteem that arise in the process of forming behavior depend on the structure of the child’s personality.